2020
DOI: 10.30534/ijatcse/2020/4791.42020
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of Untreated Bambusa Vulgaris, Gigantoch-loa Levis Gigantochloa Scortechinii, Gigantochloa Wrayi, and Schizostachyum Zollingeri Bamboo Fibers

Abstract: In the last couple decades, bamboo is getting interest due to the usefulness in textile application beside the most sustainable plant in earth. Textile fiber requires physically long, featherweight, and fine in diameter. Bamboo fibers impose high cellulose and lignin content. In a single fiber form, bamboo has very short physical length which lesser than 4 mm. This natural characteristic could affect the mechanical properties in fiber bundle or long fiber formation for textile processing. Besides, the extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Figure 4b shows the difference in average tensile strength and MOE of three bamboo species, including Dendrocalamus asper, Gigantochloa scortechinii, and Gigantochloa levis. Twenty journals focused on the tensile strength and modulus of elastic (MOE) in tensile of three bamboo species, such as Javadian et al (2019), Jais et al (2020) and Rifqi et al (2020). Based on the tensile strength graph, the Dendrocalamus asper recorded the highest average tensile strength compared to other bamboo, 226.20 MPa.…”
Section: Mechanical Characterization (Shear Tensile Compression and F...mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4b shows the difference in average tensile strength and MOE of three bamboo species, including Dendrocalamus asper, Gigantochloa scortechinii, and Gigantochloa levis. Twenty journals focused on the tensile strength and modulus of elastic (MOE) in tensile of three bamboo species, such as Javadian et al (2019), Jais et al (2020) and Rifqi et al (2020). Based on the tensile strength graph, the Dendrocalamus asper recorded the highest average tensile strength compared to other bamboo, 226.20 MPa.…”
Section: Mechanical Characterization (Shear Tensile Compression and F...mentioning
confidence: 99%
“…Mokhtar et al (2018) has suggested a different perspective with specific allocation of green and air-dried condition in proclaiming the bamboo shear strength. Studies on bamboo tensile strength have suggested that Dendrocalamus asper is the top of the list (Awalluddin et al 2017;Amatosa and Lorento 2018;Jais et al 2020), while Gigantochloa levis shows higher tensile strength than Gigantochloa scortechinii. However, more investigation is needed to expand the quality of deducing this outcome for bamboo strength grading in the future.…”
Section: Introductionmentioning
confidence: 99%